Development of UI / UX Design in Web-Based Artificial Intelligence Learning on Student Learning Motivation with a User-centered Design Approach - Masyita Insyra Putri; Erna Piantari; Enjun Junaeti (Universitas Pendidikan Indonesia, 2023)
Artificial Intelligence (AI) is a study of intelligent machines. Starting from elementary school, children should have the opportunity to learn computer science, both from computational thinking and programming. Based on that case, an e-learning platform that discusses AI with block-based programming was created, namely eCraft2Learn. Based on the results of field studies, the measurement of user experience and user interface shows the